2018
DOI: 10.55831/ajis.v3i1.73
|View full text |Cite
|
Sign up to set email alerts
|

Toward ‘Sustainable Development’ Through Zakat-Infaq-Sadaqah Distributions – As Inclusive Activities – For the Development of Social Welfare and Micro and Small Enterprises

Abstract: Indonesia’s national development, based on Pancasila as the official, foundational philosophical theory of the state, is similar to the concept of development based on an Islamic perspective, which includes economic, moral, social, material and spiritual aspects. One of the instruments used in Indonesia is the distribution of zakat (obligatory alms), infaq (donations) and sadaqah (alms) (ZIS), which eight groups of people are entitled to receive (asnaf). ZIS is a worship, which must be fulfilled by all Muslims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…These banks increased customer numbers (Arifin & Busriadi, 2020), MSMEs stimulated community economies (Triyowati & Masnita, 2015), productive business development, and short-term finance sufficiency (Ascarya, 2020). According to Mumtaz and Mahardika (2021), qard products impact the profitability of Islamic banks due to the interrelationship and this is consistent with Puspasari and Mawardi (2015) and Kholidah (2019).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…These banks increased customer numbers (Arifin & Busriadi, 2020), MSMEs stimulated community economies (Triyowati & Masnita, 2015), productive business development, and short-term finance sufficiency (Ascarya, 2020). According to Mumtaz and Mahardika (2021), qard products impact the profitability of Islamic banks due to the interrelationship and this is consistent with Puspasari and Mawardi (2015) and Kholidah (2019).…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, qard financing impacted increasing banking customers, as stated by Hannanong andAris (2018), andMukhibad et al, (2019). Yeubun et al (2021);and Triyowati and Masnita (2015) showed that the variable also affected MSME income.…”
Section: Introductionmentioning
confidence: 93%
“…Shari'ah-mode financing institutions have developed products and services, such as Islamic microfinance, which cater for the needs of marginalized communities and provides accessible loan options for individuals with limited access to traditional banking services (Abul and Sabur 2018;Effendi 2013). Furthermore, these institutions encourage the collection and distribution of zakat (obligatory alms) and the establishment of waqf (endowment) funds, which are directed towards addressing social welfare needs, such as poverty alleviation, education, and healthcare (Triyowati et al 2018). Thus, shari'ah-compliant financing is not designed for mere profit making but also to encourage social wellbeing.…”
Section: Dimensions Of Shari'ah Mode Financing and Quality Of Lifementioning
confidence: 99%
“…Hubungan secara langsung antara IPT dan asnaf pelajar memberikan kelebihan di mana pihak IPT lebih memahami keperluan dan kehendak sebenar yang diperlukan pelajar serta boleh merancang pelbagai skim bantuan dalam usaha untuk menjaga kebajikan pelajar sepanjang pengajian (Muhammad Rizal, Hairunnizam dan Sanep, 2017). Penolong amil IPT memainkan peranan penting dalam membantu asnaf pelajar untuk meneruskan pengajian di IPT dan memenuhi keperluan mereka tanpa perlu menarik diri atau menangguhkan semester atas sebab tidak mampu menampung kos pengajian (Hermein, Yolanda & Khomsiyah, 2018). Selain itu, bantuan zakat yang mencukupi akan memberi manfaat kepada pelajar kerana dapat menampung ketidakcukupan pembiayaan sedia ada untuk memenuhi perbelanjaan pengajian.…”
Section: Dapatan Dan Analisisunclassified